2016
DOI: 10.1002/cpp.2018
|View full text |Cite
|
Sign up to set email alerts
|

Group‐Based Compassion‐Focused Therapy as an Adjunct to Outpatient Treatment for Eating Disorders: A Pilot Randomized Controlled Trial

Abstract: The current study sought to assess the acceptability and feasibility of a compassion-focused therapy (CFT) group as an adjunct to evidence-based outpatient treatment for eating disorders, and to examine its preliminary efficacy relative to treatment as usual (TAU). Twenty-two outpatients with various types of eating disorders were randomly assigned to 12 weeks of TAU (n = 11) or TAU plus weekly CFT groups adapted for an eating disorder population (CFT + TAU; n = 11). Participants in both conditions completed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 47 publications
3
25
0
2
Order By: Relevance
“…Interestingly, the negative subscales (self-judgment, isolation and over-identification) showed a trend for greater improvement than the positive subscales (self-kindness, common humanity and mindfulness); in particular, over-identification (g = 0.72) and isolation (g = 0.63) had the greatest effect sizes. This echoes the results of two other papers included in this review (Kelly and Carter 2015;Kelly et al 2017) that reported larger effects for the negative compared to the positive items. Collectively, these findings speak to the debate around the psychometric properties of the SCS.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Interestingly, the negative subscales (self-judgment, isolation and over-identification) showed a trend for greater improvement than the positive subscales (self-kindness, common humanity and mindfulness); in particular, over-identification (g = 0.72) and isolation (g = 0.63) had the greatest effect sizes. This echoes the results of two other papers included in this review (Kelly and Carter 2015;Kelly et al 2017) that reported larger effects for the negative compared to the positive items. Collectively, these findings speak to the debate around the psychometric properties of the SCS.…”
Section: Discussionsupporting
confidence: 86%
“…Where an intention-to-treat sample was used, we extracted the full sample size at randomisation, and where per-protocol results were given, we took the sample size of study completers, so that the weighting of studies in the meta-analysis would be proportional to the amount of data contributed. Generally, raw means were extracted, although in two cases (Kelly and Carter 2015;Kelly et al 2017) only estimated means from multilevel modelling were reported.…”
Section: Data Extractionmentioning
confidence: 99%
See 3 more Smart Citations